Prospects for the UK Cooperation with the Scandinavian-Baltic States after Brexit - V. V. Vorotnikov (Международная аналитика)
The article is devoted to analyzing various aspects of the impact of Brexit consequences on the states of the Scandinavian-Baltic region and the prospects for relations with them. It is noted that Brexit may lead to a slowdown in the economic growth of the countries of the region, but it will not be significant. At the same time, given the small scale of the economies and their dependence on the external economic situation, the Baltic countries will experience a relatively greater negative impact than the highly developed innovative economies of the Nordic states. Revision of the priorities for the EU funding will also lead to a decrease in subsidies within the framework of the cohesion policy and the implementation of infrastructure projects, which can be painful for the economies of the Baltic states. A change in the direction of migration flows from these countries is also highly likely. As for security and defense cooperation, changes are unlikely here, since the UK has repeatedly reaffirmed its commitment to the principles of collective defense within NATO. However, a reduction in the number of channels of interaction and coordination of positions in international affairs (as a natural consequence of withdrawal from EU political institutions) is likely to intensify UK participation in other formats of regional political and defense cooperation (NB+1, JEF, NORDEFCO, etc.).